STATUS WAN ITA DALAM ISLAM: ANTARA PRINSIP SYARIAH DAN IJTIHAD FUQAHA - Ismail, Paizah (Jurnal Syariah, 2019)
This article discusses the status of woman as stated in al-Qur ’an and interpretated by muslim jurists. It concludes that there are some local cultural influences on the interpretation which must be considered in determining the status of muslim woman in nowadays society.